Removal of congo red dye from aqueous solution by bagasse / Norain Isa, Nor Aziyah Bakhari and Jaudat Hamidon - Isa, Norain; Bakhari, Nor Aziyah; Hamidon, Jaudat (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2010)
The present study deals with the utilisation of unmodified bagasse (UMB) as an adsorbent for the removal of congo red (CR) from aqueous solutions. The effect of adsorbent dosage, contact time and initial CR concentration on the adsorption are investigated. Then, the optimum conditions are applied to acid-modified bagasse (AMB) and base-modified bagasse (BMB) for comparative study. The maximum CR removal capacity by UMB, BMB and AMB are 6.813, 7.664 and 5.295 mg g⁻¹ respectively. It is found that sufficient time for adsorption equilibrium of CR is 60 min. Equilibrium isotherms for the adsorption of CR on UMB is analysed by the Langmuir and Freudlich isotherm equations. These results can be helpful in designing a batch mode system for the removal of CR from wastewater